Lacan and Cassirer. - Antoine Mooij (Value Inquiry Book Series, 2018)
The Neo-Kantian philosopher Cassirer and the psychoanalyst Lacan are two key figures in the so-called medial turn in philosophy: the notion that any form of access to reality is mediated by symbols (images, words, signifiers). This explains why the theories of both philosophers merit a description in their own unique idioms, as well as having their respective basic tenets compared. It will be argued that, rather surprisingly, these tenets turn out be complementary - actually correcting each other - based on their shared notion of man as an animal symbolicum . Its fruitfulness will be substantiated for a limited number of topics within the humanities: perception, language, politics and ethics, and mental disorder, all to be considered from this perspective.